(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To analyze factors associated with the satisfaction of outpatients who were managed and treated at Ba Vi General Hospital in 2025, thereby proposing solutions to improve the quality of medical examination and treatment services. Methods: A cross-sectional descriptive study was conducted among 400 outpatients at Ba Vi General Hospital from January to June 2025. Data were collected using a structured questionnaire developed in accordance with Circular No. 56/2024/TT-BYT on guidelines for measuring patient satisfaction and were analyzed using SPSS version 27.0. Results: The overall satisfaction rate was 83.2%; satisfaction with accessibility reached 91.3%; transparency of information and medical examination and treatment procedures reached 83.7%; facilities and medical equipment reached 78.8%; attitudes and professional competence of healthcare staff reached 80.2%; and service delivery outcomes reached 81.5%. The analysis revealed statistically significant associations between overall patient satisfaction and several factors, including gender and healthcare service delivery-related factors, namely accessibility to healthcare services, transparency of information and examination procedures, facilities and equipment, attitudes and professional competence of healthcare staff, and service delivery outcomes. Conclusion: The study indicated that the overall satisfaction level of outpatients at Ba Vi General Hospital in 2025 was relatively high (83.2%). Overall patient satisfaction was significantly associated with gender and factors related to the hospital’s healthcare service delivery process.